Flesh & blood so cheap : the Triangle fire and its legacy - Marrin, Albert (Alfred A. Knopf, 2011)
Provides a detailed account of the disastrous Triangle Shirtwaist Factory fire in New York City, which claimed the lives of 146 garment workers in 1911, and examines the impact of this event on the nation's working conditions and labor laws.